Aguila o sol - Cantinflas, 1911-1993.; Aguila, Guz.; Arvide, Manuel.; Barriero, Luis G., 1886-1947.; Boytler, Arcady, 1893-1965.; Medel, Manuel, 1906-; Mier, Felipe.; Mora, Margarita, 1920-; Tamayo, Marina. (Divisa Ediciones, 2002)
Para todos los públicos.